2004
DOI: 10.1128/iai.72.11.6633-6641.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Hyphal and Yeast Forms ofCandida albicansBind the Complement Regulator C4b-Binding Protein

Abstract: Candida albicans, an important pathogenic yeast, activates all three pathways of the complement system. To understand how this yeast evades the effects of the activated system, we have analyzed the binding of the classical pathway inhibitor C4b-binding protein (C4BP) by C. albicans. Purified native as well as recombinant C4BP bound dose dependently to the yeast and hyphal forms, as shown by multiple methods, such as confocal microscopy, flow cytometry, a novel enzyme-linked immunosorbent assay, absorption from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
96
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 59 publications
0
96
0
3
Order By: Relevance
“…In addition to inhibition of the alternative pathway, several bacteria (e.g., Moraxella catarrhalis, S. pyogenes, E. coli K1, and H. influenzae) bind C4BP and are shielded against the classical and lectin pathways (49 -51). Interestingly, many species, C. albicans, Borrelia recurrentis, and S. pyogenes, among others, have been shown to bind both FH and C4BP (26,(52)(53)(54)(55). We have recently demonstrated that non-typeable H. influenzae binds C4BP (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inhibition of the alternative pathway, several bacteria (e.g., Moraxella catarrhalis, S. pyogenes, E. coli K1, and H. influenzae) bind C4BP and are shielded against the classical and lectin pathways (49 -51). Interestingly, many species, C. albicans, Borrelia recurrentis, and S. pyogenes, among others, have been shown to bind both FH and C4BP (26,(52)(53)(54)(55). We have recently demonstrated that non-typeable H. influenzae binds C4BP (30).…”
Section: Discussionmentioning
confidence: 99%
“…Different regulators of the complement system have been shown to mediate adherence and ingestion to epithelial and endothelial cells. The binding of C4BP by C. albicans has been shown to mediate adherence to endothelial cells, and bound FHL-1 to S. pyogenes mediates and enhances the ingestion of the pathogen into epithelial cells (54,57). In fact, several studies have indicated that complement proteins and regulators are present in the respiratory tract (50,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, of all the mechanisms of complement evasion that are used by various pathogens, trapping RCA is by far the most widely disseminated strategy for avoiding the complement response. RCA recruitment is common in bacteria 16 (for example, Escherichia coli, Borrelia burgdorferi and streptococci), but has also been described for viruses 17 (for example, HIV-1), fungi 18,19 (for example, Candida albicans) and parasites 20 (for example, Echinococcus spp.) (Supplementary information S1 (table)).…”
Section: Making Use Of the Host's Arsenal -Acquiring Regulatorsmentioning
confidence: 99%
“…Expression of M protein is important for the ability of S. pyogenes to cause the diseases associated with this pathogen: acute pharyngitis and impetigo (6). Many other pathogens share the ability to sequester C4BP (7)(8)(9)(10)(11)(12). Thus escape from complement attack by hijacking of C4BP is emerging as a widespread contributor to immune evasion strategies and is a therapeutic target.…”
mentioning
confidence: 99%